2006
DOI: 10.1111/j.1742-4658.2006.05490.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Dps protein from the thermophilic cyanobacterium Thermosynechococcus elongatus

Abstract: DNA‐binding proteins from starved cells (Dps proteins) protect bacteria primarily from oxidative damage. They are composed of 12 identical subunits assembled with 23‐symmetry to form a compact cage‐like structure known to be stable at temperatures > 70 °C and over a wide pH range. Thermosynechococcus elongatus Dps thermostability is increased dramatically relative to mesophilic Dps proteins. Hydrophobic interactions at the dimeric and trimeric interfaces called Dps‐like are replaced by salt bridges and hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 45 publications
2
43
1
Order By: Relevance
“…3). These data are in agreement with the results reported for other Dps family proteins (Franceschini et al, 2006;Zhao et al, 2002). However, they are contrary to the results obtained using an Nterminal 10|His-tagged form of CjDps (Huergo et al, 2013).…”
Section: Effects Of H25g/h37g Substitution On Iron Oxidation Activitycontrasting
confidence: 57%
See 2 more Smart Citations
“…3). These data are in agreement with the results reported for other Dps family proteins (Franceschini et al, 2006;Zhao et al, 2002). However, they are contrary to the results obtained using an Nterminal 10|His-tagged form of CjDps (Huergo et al, 2013).…”
Section: Effects Of H25g/h37g Substitution On Iron Oxidation Activitycontrasting
confidence: 57%
“…1b, c). The Dps FOC is known to contain two metal-binding sites with a different affinity for Fe 2+ ions (Franceschini et al, 2006 (Chiancone & Ceci, 2010). In Escherichia coli Dps, the reaction rate increases 100-fold in the presence of H 2 O 2 (Zhao et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In H. pylori Dps, D. radiodurans Dps1 and A. tumefaciens Dps structures, only the A site contains iron whereas the B site contains a water molecule (Ceci et al, 2003;Romão et al, 2006;Zanotti et al, 2002). In E. coli Dps (Grant et al, 1998) and T. elongatus Dps both sites are occupied by two water molecules (Franceschini et al, 2006). These data indicate that the two metal binding sites A and B have different affinity for iron, and that the second metal coordination shell, formed by residues that are not directly in contact with the metal but interact with metal binding site residues, may influence the affinity for iron.…”
Section: Fig 3cmentioning
confidence: 99%
“…Dps1 and Dps2 have been extensively characterized in vitro (26,29,37). These studies have shown that their reactivity with H 2 O 2 and O 2 is in striking contrast to that of the Dps proteins characterized in other organisms (26), which generally use H 2 O 2 as the preferred iron oxidant with an ϳ100-to 1,000-fold preference over O 2 (11,38,41 (26), and it may function as both a detoxifying enzyme and an iron storage protein.…”
mentioning
confidence: 99%